Component analysis of nutritionally rich chloroplasts: recovery from conventional and unconventional green plant species - Gedi, Mohamed A.; Briars, Rhianna; Yuseli, Felius; Zainol, Noorazwani; Darwish, Randa; Salter, Andrew M.; Gray, David A. (Springer, 2017)
A study of the literature indicates that chloroplasts synthesise a range of molecules, many of which have nutritional value for humans, but as yet no one has established the nutritional credentials of chloroplasts recovered from plant cells. Chloroplast-rich-fractions (CRFs) were prepared from green plant species and the macro- and micronutrient composition compared with the whole leaf materials (WLMs). The results indicated that, on a dry weight basis, CRF material from a range of green biomass was enriched in lipids and proteins, and in a range of micronutrients compared with the WLM. Vitamins E, pro-vitamin A, and lutein were all greater in CRF preparations. Of the minerals, iron was most notably concentrated in CRF. Spinach CRFs possessed the highest α-tocopherol (62 mg 100 g-1 , dry weight (DW)), β-carotene (336 mg 100 g- 1 DW) and lutein (341 mg 100 g-1 DW) contents, whilst grass CRFs had the highest concentration of alpha-linolenic acid (ALA) (69.5 mg g-1). The higher concentrations of α-tocopherol, β-carotene, lutein, ALA and trace minerals (Fe and Mn) in CRFs suggest their potential use as concentrated ingredients in food formulations deficient in these nutrients.